Academic Learning Outcome And Creative Thinking Skills On Projectile Motion Topic - John Rafafy Batlolona; Natcha Mahapoonyanont (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
PBL is one of the constructive learning models. Therefore, the purpose of this study was to find out whether PBL was more effective in enhancing academic learning outcomes and creative thinking skills with different classes. This research was began by compiling instruments, carrying out the learning process, analyzing data, and presenting it in the form of reports. The results showed that the average value of student learning achievement was 73.29 in the experimental class and 74.40 in the control class. This average value was then tested by the hypothesis using the right tailed T-test. The right tailed T-test was used to find out whether the learning achievements of students taught with PBL were higher than those taught conventionally were. Through the T-test with the help of SPSS, the results of tcount 0.514 obtained < ttable 1,670. Conclusions from the results of the analysis show that the learning achievement of the experimental class students is smaller or equal to the control class. Data on creative skills were tested by precise nonparametric analysis, the Mann-Whitney test because data was not normally distributed. Through the Mann-Whitney analysis with the assistance of SPSS, it was obtained z values for creative thinking skills 5,608> 1,65 for creative thinking skills data. This means that the creative skills of students taught by PBL were higher than those taught conventionally were.